Peer review in forensic science. (August 2017) - Ballantyne, Kaye N.; Edmond, Gary; Found, Bryan
Highlights: A review of peer review. A critical review of peer review and verification in the forensic sciences. A typology of different types of peer review and their potential uses and limits. Recommendations on the use of peer review and verification. Recommendations on improving transparency in forensic science reporting. Abstract: Peer review features prominently in the forensic sciences. Drawing on recent research and studies, this article examines different types of peer review, specifically: editorial peer review; peer review by the scientific community; technical and administrative review; and verification (and replication). The article reviews the different meanings of these quite disparate activities and their utility in relation to enhancing performance and reducing error. It explains how forensic practitioners should approach and use peer review, as well as how it should be described in expert reports and oral testimony. While peer review has considerable potential, and is a key component of modern quality management systems, its actual value in most forensic science settings has yet to be determined. In consequence, forensic practitioners should reflect on why they use specific review procedures and endeavour to make their actual practices and their potential value transparent to consumers; whether investigators, lawyers, jurors or judges. Claims that review increases the validity of a scientific technique or accuracy of opinions within a particular case should be avoided until empirical evidence is available to support such assertions.